Percorsi, flussi e persone nella progettazione ospedaliera L'analisi configurazionale, teoria e applicazione - Setola, Nicoletta (Strumenti per la didattica e la ricerca, 2013)
What does it mean to design hospitals according to the flows while satisfying the users' needs? How do the different parts of the hospital body bind together? When can a spatial and functional relationship be rightly defined as close, adjacent or distant? How difficult is it to walk along a connection? The volume reconstructs the state of the art on the theme of people flows in hospitals, and identifies tools to support the project and management of the flow system within hospitals. In particular, it presents the innovative approach Space Syntax, born in the Anglo-Saxon world and used for highly complex building projects. The book offers an original contribution in a sector in which the need for studies combining research and professional activity has arisen.